Relationship between Polyphagotarsonemus latus (Acari: Tarsonemidae) and the papaya ringspot virus (PRSV-p) - ALCANTARA-J., JOSÉ ANGEL; SANTILLÁN-GALICIA, MA. TERESA; OTERO-COLINA, GABRIEL; MORA-A., ANTONIO; GUTIÉRREZ-E., M. ALEJANDRA; HERNÁNDEZ-C., ELÍAS (Revista Colombiana de Entomología, 2011)
Polyphagotarsonemus latus is a cosmopolitan species that affects several crops in tropical and temperate areas. The main damage caused by the infestation of this species is the reduction or deformation of young leaves, buds, fruits and flowers. When P. latus feeds on young papaya leaves, these present chlorosis and down curled distorted areas. In Mexico, the damage caused by this mite is called “monkey´s hand” because the area of the young papaya leaves is reduced leaving only the veins visible. This damage is similar to the symptoms caused by the infection of Papaya ringspot virus-p (PRSV-p). As P. latus and PRSV-p may cause similar damage to papaya leaves, the aim of this investigation was to determine the effect of P. latus, PRSV-p and their possible interaction in the reduction of foliar area. The diagnosis of PRSV-p was done by RT-PCR. The results showed that the effect produced by P. latus and PRSV-p were similar; however, the mites were found only on the younger leaves. As a result, the damage was observed only on these leaves, the chlorosis produced by the mites started in the central vein towards the end of the leaves; on the contrary, the damage of the virus can be found in any part of the leaves. The height and diameter of the stems in the plants were affected only by the infestation of the mites, as no difference was found on plants inoculated with PRSV-p.